2000
DOI: 10.1007/s007050070116
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of the S7 gene does not segregate Chinese strains of bluetongue virus into a single topotype

Abstract: Bluetongue virus (BTV) infection of ruminants is endemic throughout tropical and subtropical regions of the world. The S7 gene segments of prototype Chinese strains of BTV serotypes 1, 2, 3, 4, 12, 15, and 16 were sequenced and compared to the same genes of prototype strains of BTV from the US, Australia, and South Africa. The S7 genes and predicted VP7 proteins of the Chinese viruses were relatively conserved, with the notable exception of serotype 15. Furthermore, phylogenetic analysis of the S7 genes did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Therefore, it should be necessary to pay attention to the potential influence of intragenic recombination on its biology and epidemiology. Among the viral proteins, NS3 is proposed to be associated with the transmission of the virus in different insect populations and species (4,5,35), and VP7 is also thought to be related to the infection of insect populations (9,55). In the present study, stable and genetic vp7 and ns3 mosaics were found, suggesting that insects might be more permissive for the events leading to intragenic recombination as well, making insects an important diversitygenerating host.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Therefore, it should be necessary to pay attention to the potential influence of intragenic recombination on its biology and epidemiology. Among the viral proteins, NS3 is proposed to be associated with the transmission of the virus in different insect populations and species (4,5,35), and VP7 is also thought to be related to the infection of insect populations (9,55). In the present study, stable and genetic vp7 and ns3 mosaics were found, suggesting that insects might be more permissive for the events leading to intragenic recombination as well, making insects an important diversitygenerating host.…”
Section: Discussionsupporting
confidence: 50%
“…VP7 is encoded by Seg-7 and plays some key roles in virus replication, such as forming the surface of the core and being responsible for core entry into insect cells (46). As the outer core protein, VP7 is the major serogroup-specific antigen and shows variations that are considered to be associated with the insect populations that act as vectors for different virus strains in different geographic areas (9,55). All available 88 VP7 sequences constituted five lineages (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Genome segments 7 and 10, encoding VP7 and NS3, show intermediate levels of variation, dividing isolates into a number of clades that show only partial correlation with virus topotype [13]. The remaining variations in Seg-7 and Seg-10 have as yet unconfirmed significance, although it has been suggested that they may relate to transmission of the virus by different insect vector species/populations [13], [39], [40,]. The remaining six genome segments (Seg-1, -3, -4, -5, -8 and 9; encoding VP1, VP3, VP4, NS1, NS2 and VP6, respectively) are all highly conserved, showing variations that correlate primarily with virus origin, dividing isolates into eastern and western topotypes and providing evidence of geographic subgroups, but no significant correlation with virus serotype (supplementary data, [13]).…”
Section: Introductionmentioning
confidence: 99%
“…It seems that recombination is more probable in regions of the genome that are able to form secondary structures. It has been shown that genetic variation of the VP7 and NS3/A proteins may influence the transmission of BTV by different midge populations endemic to different geographic regions [211][212][213][214]. As mentioned above, BTV is transmitted by certain species of Culicoides midges, with the most important being Culicoides imicola in Asia, Africa and southern Europe.…”
Section: • Reoviridae Blue Tongue Virusmentioning
confidence: 95%